Relationship between cool and hot executive function in young children: A near‐infrared spectroscopy study - Moriguchi, Yusuke (Developmental science, 2022)
A theoretical distinction exists between the cool and hot aspects of executive function (EF). At the neural level, cool EF may be associated with activation in the lateral prefrontal cortex and the anterior cingulate cortex, whereas the orbitofrontal cortex may play a key role in hot EF. However, some recent studies have shown that young children show activity in the lateral prefrontal regions during hot EF tasks, suggesting that the distinction between hot and cool EF may not be as marked. Nevertheless, few neuroimaging studies have directly examined the relationship between cool and hot EF. In this study, preschool children (N = 46, mean age = 66.1 months) were given both cool (Dimensional Change Card Sort (DCCS) and Stroop‐like tasks) and hot (delay of gratification) EF tasks, and neural activation during these tasks was measured using functional near‐infrared spectroscopy (fNIRS). Correlational analyses and analysis of variance (ANOVA) were conducted to assess the relationship between cool and hot EF. At the behavioral level, a moderate correlation was found between DCCS and Stroop‐like tasks, but no correlation emerged between cool and hot EF tasks. At the neural level, prefrontal activations during the cool EF tasks did not correlate with those during the hot EF task. Further, children showed stronger prefrontal activations during the DCCS tasks compared to the delay of gratification tasks. The results suggest that the neural basis of hot and cool EF may differ during early childhood.